2016
DOI: 10.1177/1479164116653239
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gamma-carboxylase inhibition on serum osteocalcin may be partially protective against developing diabetic cardiomyopathy in type 2 diabetic rats

Abstract: Aims: To investigate the possible protective effect of elevated undercarboxylated osteocalcin on diabetic cardiomyopathy mechanisms and risk factors. Methods: In all, 32 male rats were divided into four groups: control, diabetic, diabetic warfarin and normal warfarintreated groups. Isolated heart functions were assessed; fasting serum insulin, glucose and glycosylated haemoglobin, homeostasis model assessment insulin resistance and lipid profile were investigated. Serum undercarboxylated osteocalcin and adipon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Thus, there is a previously postulated mechanism for warfarin to lower blood glucose. Although warfarin's effects on blood glucose have not been studied in human trials, in diabetic rats, it increases insulin secretion and reduces fasting glucose . Moreover, a positive feedback loop has been postulated in which uncarboxylated osteocalcin stimulates insulin secretion, which further stimulates osteoblasts to produce uncarboxylated osteocalcin, the metabolism of which is inhibited by warfarin .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, there is a previously postulated mechanism for warfarin to lower blood glucose. Although warfarin's effects on blood glucose have not been studied in human trials, in diabetic rats, it increases insulin secretion and reduces fasting glucose . Moreover, a positive feedback loop has been postulated in which uncarboxylated osteocalcin stimulates insulin secretion, which further stimulates osteoblasts to produce uncarboxylated osteocalcin, the metabolism of which is inhibited by warfarin .…”
Section: Discussionmentioning
confidence: 99%
“…Although warfarin's effects on blood glucose have not been studied in human trials, 19 in diabetic rats, it increases insulin secretion and reduces fasting glucose. 22 Moreover, a positive feedback loop has been postulated in which uncarboxylated osteocalcin stimulates insulin secretion, which further stimulates osteoblasts to produce uncarboxylated osteocalcin, the metabolism of which is inhibited by warfarin. 19 Such a positive feedback loop would be expected to result in a more marked hypoglycemic effect of warfarin after prolonged exposure, as is seen in Figure 1.…”
Section: Discussionmentioning
confidence: 99%
“…17 Osteocalcin could exert a protective effect on cardiovascular risk in diabetic patients by improving glucose tolerance and hyperlipidaemia. [18][19][20] While our previous studies have illustrated the antioxidative and antiapoptotic role of undercarboxylated osteocalcin (ucOC) in protecting the diabetic heart from developing DCM, 18 the present study is the first, to the best of our knowledge, to investigate the potential role of ucOC as a therapeutic agent for DCM and to document the relationships among increased ucOC, upregulation of VEGF expression, improvement in myocardial microcirculation, and its subsequent cardiac functional and histopathological changes.…”
Section: Introductionmentioning
confidence: 84%
“…Serum osteocalcin may play an important role in protecting myocardial cells by binding with the GPRC6A receptor. The mechanism of the protection against cardiomyopathy mediated by osteocalcin in mice with type 2 diabetes was studied by Gamal et al [27]. These authors found that serum osteocalcin levels and serum adiponectin levels in the diabetes group were much lower than the levels in the control group.…”
Section: Discussionmentioning
confidence: 99%